Integrating CBPR and Implementation Science to Develop a PrEP-Promotion Intervention for Black Transgender Women. - Rhodes, Scott D.; Mann-Jackson, Lilli; Alonzo, Jorge; Aguilar-Palma, Sandy K.; Neffa Creech, Deborah; Keatley, JoAnne G.; Smart, Benjamin D.; Montoya, Jorge (Health Education & Behavior, 2026)
Black/African American transgender (trans) women experience disproportionately high rates of HIV, yet few evidence-based interventions are designed specifically for them. This study outlines the development of the Sisters United intervention through the adaptation of ChiCAS, an evidence-based intervention for trans Latinas. Sisters United promotes use of pre-exposure prophylaxis (PrEP), condoms, and medically supervised gender-affirming hormone therapy (GAHT) among Black/African American trans women. Integrating community-based participatory research and implementation science, our systematic process included multiple steps conducted in partnership with a steering committee of Black/African American trans women, other community representatives, scientists, practitioners, and consultants. We held focus groups and obtained iterative feedback about intervention objectives, messaging, and activities, including new activities focused on medical mistrust and the use of injectable PrEP, to guide the adaptation. Key intervention components developed through this process include an implementation manual, facilitator's guides for in-person and virtual delivery, video segments, and an e-learning course to support effective implementation. Like the original ChiCAS intervention, Sisters United is designed to be delivered in two sessions, with a focus on raising awareness about HIV and GAHT, building condom use skills, and overcoming barriers to health care. This intervention fills a critical gap by offering a scalable solution to promote HIV health equity among Black/African American trans women. Moreover, our systematic process can serve as a guide for others developing, refining, or adapting interventions to meet the needs of a new community or population and/or infuse updated information and innovations into an existing intervention.